2012
DOI: 10.5588/ijtld.11.0778
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of tuberculosis in elderly versus young hospitalised patients in Amritsar, India

Abstract: The presentation of TB in elderly patients differs from that of younger patients in symptomatology. A high index of suspicion is therefore required to make a timely diagnosis of TB in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…A higher proportion of elderly males (46%vs 37%) were smokers in this study. A study from Amritsar among hospitalised TB patients showed no difference in smoking between the elderly and younger [10] while a descriptive study in a cohort of 100 patients aged >50 yrs from Himachal Pradesh documented 68% smoking [11]. Smoking cessation interventions focusing on the elderly will be important to reduce the burden of complications due to TB.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of elderly males (46%vs 37%) were smokers in this study. A study from Amritsar among hospitalised TB patients showed no difference in smoking between the elderly and younger [10] while a descriptive study in a cohort of 100 patients aged >50 yrs from Himachal Pradesh documented 68% smoking [11]. Smoking cessation interventions focusing on the elderly will be important to reduce the burden of complications due to TB.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of TB in this age group may become an important source of infection and perpetuate the pool of infection in the community. Though previous studies in India between 1996 and 2005 have described poor treatment outcomes in this age group, these were conducted either in a tertiary care setting or were limited to a small geographical area [3], [5], [13]–[15]. Association of important factors including the type of TB, HIV status, type of DOT (Directly Observed Treatment) provider (a health care provider administering treatment and providing patient support) have not been studied in great detail in older TB patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 TB may present and manifest itself differently in older compared with younger adults. 4 Furthermore, older adults are at high risk of non-communicable diseases, especially diabetes mellitus. It is well established that the risk of TB among people with diabetes increases by two-to three-fold, 5 with those who later develop TB having poorer treatment outcomes.…”
Section: Tuberculosis Case Burden and Treatment Outcomes In Childrenmentioning
confidence: 99%
“…Tagaro, 1 A. D. Harries, 2,3 B. Kool, 4 S. Ram, 5 K. Viney, 6 B. Marais, 7 L. Tarivonda 8 V anuatu is an island country located in the South Pacific. The National Tuberculosis Programme (NTP) was started in Vanuatu in the early 1980s, and the DOTS strategy 1 was introduced in 1999.…”
Section: Tuberculosis Case Burden and Treatment Outcomes In Childrenmentioning
confidence: 99%